2016
DOI: 10.1097/md.0000000000004115
|View full text |Cite
|
Sign up to set email alerts
|

The trends of utilization in traditional Chinese medicine in Taiwan from 2000 to 2010

Abstract: Introduction:There is no study exploring the trend of utilization in traditional Chinese medicine (TCM) from 2000 to 2010. The objective of this study was to investigate the trends of TCM utilization among 3 cross-sectional cohorts of 2000, 2005, and 2010.Method:This study was a cross-sectional analysis of TCM utilization over time. We compared the mean TCM visits among 3 cohorts of 2000, 2005, and 2010. We derived 3 randomly sampled cohorts of nearly 1 million representative beneficiaries in each of 2000, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
1
41
1
Order By: Relevance
“…A previous study on the characteristics of acupuncture users in Taiwan demonstrated that the ratio of acupuncture users was fairly stable during the first few years of the establishment of the NHI program (from 6% in 1996 to 6.2% in 2002) [ 29 ]. However, our study revealed that from 2002 to 2011, acupuncture utilization increased further from 7.98% to 10.9%, which was consistent with the increasing trend in overall TCM users in Taiwan (from 26.59% in 2000 to 28.66% in 2010) [ 3 ]. The percentage of acupuncture usage in Taiwan was higher than that in Japan (6.7% in 2006) [ 4 ], Australia (3.4% in 2011) [ 30 ], the U.S.A. (1.5% in 2007) [ 9 ], the UK (1.6% in 2004) [ 31 ] and South Korea (7.4%) [ 6 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A previous study on the characteristics of acupuncture users in Taiwan demonstrated that the ratio of acupuncture users was fairly stable during the first few years of the establishment of the NHI program (from 6% in 1996 to 6.2% in 2002) [ 29 ]. However, our study revealed that from 2002 to 2011, acupuncture utilization increased further from 7.98% to 10.9%, which was consistent with the increasing trend in overall TCM users in Taiwan (from 26.59% in 2000 to 28.66% in 2010) [ 3 ]. The percentage of acupuncture usage in Taiwan was higher than that in Japan (6.7% in 2006) [ 4 ], Australia (3.4% in 2011) [ 30 ], the U.S.A. (1.5% in 2007) [ 9 ], the UK (1.6% in 2004) [ 31 ] and South Korea (7.4%) [ 6 ].…”
Section: Discussionsupporting
confidence: 76%
“…Of the different types of CAM, traditional Chinese medicine (TCM) has been well defined as an ancient medical system by the National Center for Complementary and Integrative Health (NCCIH, U.S.A.) [ 2 ]. The trends in TCM utilization have also increased gradually in Taiwan, and more than 28% of Taiwanese consulted a TCM service in 2010 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, TCM use in patients with AD was still lower than that in patients with other chronic illnesses, such as allergic rhinitis and asthma . Patients with neurogenic disorders, including AD, had a low utilization rate of TCM . One of the possibilities is that there was limited clinical evidence to report the efficacy of TCM in the treatment of AD.…”
Section: Discussionmentioning
confidence: 99%
“…뿐만 아니라 국민건강보험제도 등 의료제도적 94) In 1997∼2011, 14.28% of the patients visited the TEAM clinic for SLE treatment 95) Diseases of the genitourinary system (16.49%) Menopausal syndrome In 1997∼2004, 64.9% of 45∼55 year old women had experience using TEAM 96) In 2002, 75.1% of patients diagnosed with menopausal syndrome had experience using TEAM 97) Infertility In 2000∼2011, 96.17% of patients diagnosed with infertility had experience using TEAM 98) Renal 104) *In parentheses, frequency of use of TEAM for Western medicine use by ICD-9 disease classification. Extracted from Yuh-Hsiang Yeh et al 105) . Table II.…”
Section: 대만의 보편적 Team 이용 관련 연구mentioning
confidence: 99%